2006
DOI: 10.2478/s11756-006-0169-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of forest and grassland vegetation on soil hydrology in Mátra Mountains (Hungary)

Abstract: Water retention characteristics, rainfall, throughfall and soil water content dynamics were investigated in a low mountain area to compare a forest and a grassland. The soil water retention curve of the topsoil has similar shape in both studied areas, however that of the deeper soil layer shows more difference. We determined the precipitation depth, duration and intensity values of rainfall events. The relationship between rainfall and throughfall depth was described in linear regressions. Interception was cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 6 publications
0
9
0
2
Order By: Relevance
“…Vegetation cover directly affects the soil-moisture regime and thus the hydrological behavior of a watershed. SMC can be higher for forests than for grassland, but not always [ 20 – 22 ]. Peng [ 23 ] reported that the average annual SMC in the Heihe River basin is about 50% higher in spruce forest than in grassland.…”
Section: Discussionmentioning
confidence: 99%
“…Vegetation cover directly affects the soil-moisture regime and thus the hydrological behavior of a watershed. SMC can be higher for forests than for grassland, but not always [ 20 – 22 ]. Peng [ 23 ] reported that the average annual SMC in the Heihe River basin is about 50% higher in spruce forest than in grassland.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, producing stemflow with a greater amount in a more efficient manner might be an effective strategy to utilize precipitation by reducing the evaporation loss (Devitt and Smith, 2002;Li et al, 2009), acquire water (Murakami, 2009) and withstand drought (Martinez-Meza and Whitford, 1996). However, because stemflow occurs in a small amount, some studies neglected the dynamics of stemflow yield by setting a fixed percentage of incident precipitation in the range of 1-8 % (Dykes, 1997;Germer et al, 2006;Hagy et al, 2006) or even ignored stemflow while computing the water balance of terrestrial ecosystems (Llorens and Domingo, 2007;Zhang et al, 2016). That underestimated its disproportionately high influence on xerophytic shrub species (Andersson, 1991;Levia and Frost, 2003;.…”
Section: Yuan Et Al: Comparisons Of Stemflow and Its Bio-/abioticmentioning
confidence: 99%
“…Deutsch et al (2010) observaron que la humedad del suelo bajo sequía severa limita la producción de los pastizales templados-fríos, los cambios en los niveles de humedad del suelo variaron en concordancia al grado de degradación del suelo (Snymana & Preez, 2005), siendo la lluvia la única fuente de recarga de agua; la textura, cubierta vegetal, y elevación influyen en el contenido de humedad del suelo (Salve & Allen-Diaz, 2001). La dinámica de la humedad del suelo mostraron tendencias similares en los perfiles del suelo de bosques y del pastizal con secado más intenso en el bosque durante la temporada de crecimiento, posiblemente por la mayor utilización de agua en las capas por los árboles (Hagyó et al, 2006). De manera que la función de los tipos de vegetación es afectada por la distribución de agua disponible en el suelo y la composición florística del pastizal (Breshears & Barnes, 1999).…”
Section: Resultados Y Discusiónunclassified